Geographic and genetic structure of African oil palm diversity suggests new approaches to breeding - (:unkn) unknown (My University, 2009)
Since the 1960s, there has been very little diversification of oil palm (Elaeis guineensis) seed production, with mainly Deli x La M, and Deli x Congo type crosses. The Deli origin, which was introduced from Africa into Indonesia in 1848, is unavoidable in breeding. In order to understand the complementarity between the Africa and "Asia" origins, and to diversify the genetic base of oil palm production, the structure of the genetic resources involved in the history of oil palm breeding in relation to African germplasm including subspontaneous populations needs to be understood. In this study, 318 individuals from 26 origins and eight countries were analysed with 14 microsatellite loci. Descriptive and Bayesian analyses of oil palm genetic diversity (Principal Coordinates Analysis, Neighbour-Joining Tree and Structure software) revealed two original groups which reflected the discontinuity of African species at the Dahomey Gap, West Africa (Group I) on the one hand, and "Benin-Nigeria-Cameroon-Congo-Angola" (Group II) on the other hand. The Deli group (Group III), derived from group II, is the result of artificial selection (mass selection). The genetic structuring revealed showed the positive contribution of the within-population mass selection practiced in the Deli population, and explains the success of Deli x La M, and Deli x Congo crosses. A selection strategy is proposed, based on the yet-to-be-exploited complementarity that exists between the two African genetic groups and on within-group improvement. We suggest (Deli x Group II) x Group I crosses, so that group II benefits from the quality of the Deli origin
Keywords: African Research